Imaging characteristics of central neurocytomas according to Ki-67 proliferation index - Zhang, Yan-li; Liu, Ling; Li, Wei; Ran, Chao; Luo, Yu-qi (Frontiers in Oncology, 2025)
PurposeTo evaluate the imaging characteristics of central neurocytoma (CN) with different Ki-67 indices and reveal its biological behavior.Materials and methodsSixty-nine cases of intraventricular CN confirmed by histopathology were collected retrospectively. According to Ki-67 indices, they were divided into CNs with high Ki-67 (30 cases) and CNs with low Ki-67 (39 cases). Their clinical and imaging findings were compared and analyzed.ResultsCompared to CNs with low Ki-67, CNs with high Ki-67 were larger (P < 0.001) and more solid (P = 0.019). Restricted diffusion (P = 0.020), CT hyperdensity (P < 0.001), abnormal vessels (P = 0.018), and marked MRI enhancement (P < 0.001) were more common in CNs with high Ki-67.ConclusionDifferent Ki-67 indices could affect the imaging characteristics of CNs. Tumor size, radiologic solidity, abnormal vessels, and marked MRI enhancement suggested CNs with high Ki-67. Combining these imaging characteristics and Ki-67 indices offered meaningful insights into their clinical diagnosis and biological behavior.